The Relevance of Catholic Theological Inspiration on Ecumenical Dialogue for Religious Moderation in Indonesia - Tedjoworo, Hadrianus (International Journal of Nusantara Islam, 2025)
Ecumenical dialogue is part of the post-Vatican Council II Catholic theological practice that emphasizes the importance of openness to other traditions and a shared search for truth. In the Indonesian context, which is characterized by religious diversity and the challenges of intolerance and fundamentalism, Catholic theological reflection can make an important contribution to strengthening religious moderation. This study aims to identify and correlate Catholic theological ideas on ecumenical dialogue that can be the basis for developing a relevant and contextual interfaith dialogue methodology. Using a content analysis approach and correlation of theological ideas based on an integrative literature review, this study examines Church documents, the views of Catholic theologians Yves Congar, Walter Kasper, and John Paul II, and research results that discuss interreligious moderation. The results of the study indicate that receptive ecumenism, mutual spiritual enrichment, inner reform, shared witness, and learning through dialogue can be the foundation of a methodological framework for dialogue in religious moderation without losing the integrity of each faith. The practice of interfaith dialogue in Indonesia can be enriched with a transformative approach that emphasizes reciprocal learning, shared reflection of faith, and acceptance of diversity. The contribution of this research is primarily a fresh perspective and methodology in the contextual theological study of dialogue, emphasizing that Catholic theological inspirations can be used as material for compiling a program framework to advance religious moderation.